Primary Central Nervous System Histiocytic Sarcoma Arising After Precursor B-Cell Acute Lymphoblastic Leukemia. Issue 12 (December 2015) - Brown, Alan F.; Fan, Hongxin; Floyd, John R.; Henry, James M.; Higgins, Russell A.
Abstract : Abstract: Histiocytic sarcomas (HSs) are rare malignant neoplasms derived from histiocytes that may be associated with other hematolymphoid neoplasms. Histiocytic sarcomas rarely occur in the CNS and have not previously been reported in conjunction with prior B-cell lymphoblastic leukemia. We report the case of a 23-year-old man who presented with primary CNS HS 7 years after achieving remission for precursor B-cell acute lymphoblastic leukemia (B-ALL). Molecular studies revealed clonal immunoglobulin heavy-chain ( IGH) gene rearrangement within the HS, suggesting linkage to his previous B-ALL. Previously reported post-ALL HSs show a strong predilection for young males (male-to-female ratio, 20:1), whereas cases of primary CNS HS without previous ALL affected older adults with balanced sex predilection. The patient's survival at 60 months exceeds expectations when compared with that of other reported cases of de novo primary CNS HS (n = 18) and post-ALL HS at all sites (n = 19). In addition, we discuss the potential relationship between B-ALL and HS posed by other authors.